Erandamooladi Dhooma Nasya in Ardhavabhedaka (Migraine): A Single- Arm Pilot Feasibility Clinical Trial - Dr. Divya Mishra; Dr. Dinesh Patil (The Bioscan, 2026)
Background: Migraine is a recurrent neurological disorder characterized by episodic headache attacks, often accompanied by nausea, sensitivity to light, and sensitivity to sound. In Ayurvedic literature, a comparable condition is described as Ardhavabhedaka (migraine). Nasya Karma is traditionally indicated for diseases of the head region, and Dhooma Nasya (medicated fume inhalation) is a specialized modality in which medicated smoke is administered through the nostrils. Objective: To assess the feasibility, safety, and preliminary clinical outcomes of Erandamooladi Dhooma Nasya in patients suffering from Ardhavabhedaka (migraine). Methods: A prospective single-arm pilot feasibility trial was conducted in ten patients diagnosed with migraine corresponding to Ardhavabhedaka. Erandamooladi Dhooma Nasya was administered once daily (3 puffs per nostril) before food for 7 consecutive days. Clinical outcomes were evaluated using the Visual Analogue Scale (VAS) for pain intensity and the Migraine Disability Assessment Scale (MIDAS). Assessments were performed at baseline, immediately after completion of therapy, and during two follow-up visits. Results: All ten participants completed the treatment schedule and the scheduled follow-ups, indicating complete adherence and retention during the study period. A progressive reduction in headache intensity and migraine-related disability was observed following the intervention. The mean VAS score decreased from 5.6 at baseline to 3.2 after treatment and further reduced to 2.3 at the second follow-up. Similarly, the mean MIDAS score declined from 14.0 at baseline to 12.6 after treatment, reaching 10.7 at the final follow-up. Two participants experienced complete remission of symptoms, six demonstrated marked improvement, and two showed moderate improvement. No adverse events were reported during the treatment or follow-up period. Conclusion: Erandamooladi Dhooma Nasya was feasible to administer and well tolerated in this pilot sample. The intervention showed encouraging trends toward improvement in migraine intensity and disability, supporting the need for larger controlled trials.